Large scale treasure hunt games assisted by an augmented reality system - Felgueiras, Gilberto (2013)
This paper presents and describes the implementation of an augmented reality system to assist a user in a treasure hunt gaming activity. The concept proposed here, essentially serves to support a practitioner of a form of territorial exploitation. The case study applies to global scale territories where a large number of 'treasures' are hidden in different locations for a subsequent hunt. The developed application provides two modules of augmented reality, one based on GPS coordinates provided by the current smartphones, the other in the extraction of additional information of treasure. This extraction uses two-dimensional quick response codes (QR Code), to serve two purposes; provide additional information to the treasure hunt be used as a augmented reality marker. The results are quite encouraging thus enabling the continuation of this project in the near future.